Forest fuel extraction does not affect macrolichens on deadwood substrates, but only if coarse woody debris is not collected - Purhonen, Jenna; Nirhamo, Aleksi; Jäntti, Mari; Halme, Panu (Springer, 2025)
The increasing use of forest fuels poses risks to biodiversity. Lichens that grow on deadwood may be affected as fuel extraction removes their substrates. We surveyed deadwood and macrolichens on deadwood in two types of clearcuts: sites in which forest fuels, stumps and slash, had been extracted, and standard clearcut sites, i.e. control sites with no fuel extraction. Extraction sites had 52% lower deadwood volume (44.3 m³/ha vs. 21.4 m³/ha) and 36% less deadwood surface area. However, the negative impact of fuel extraction on macrolichen species richness was low: 21.4 and 16.9 species on average were found in control and extraction sites, respectively. We found a clear positive relationship between macrolichen species richness and the surface area of logs, which are usually not targeted by forest fuel extraction. Species composition varied more among extraction sites than control sites and differed between all the studied deadwood types. Species of Cladonia were associated with stumps, while species in the family Parmeliaceae were associated with logs. Slash was of negligible importance to macrolichens. Stumps may hold value, particularly if large-sized deadwood is otherwise not available. Thus, we conclude that the extraction of slash poses no threat to macrolichen diversity, whereas extensive extraction of stumps can cause losses in lichen diversity. The loss of coarse woody debris during forest fuel extraction has negative effects on lichen diversity and should be avoided.